The Covid-19 Pandemic and Lockdown: First Order Effects on Gender Gaps in Employment and Domestic Time Use in India - Ashwini Deshpande (Global Labor Organization (GLO), 2020)
Based on national-level panel data from Centre for Monitoring Indian Economy (CMIE)'s Consumer Pyramids Household Survey (CPHS) database, this paper investigates the first effects of Covid-19 induced lockdown on employment and the gendered pattern of time allocation inside the home. Examining the employment status during the last 12 months of over 40,000 individuals surveyed in April 2020 (i.e. during the strict nationwide lockdown), the paper finds that overall employment, which was relatively stable during the pre-pandemic time period, dropped sharply post-lockdown. This drop in employment was not gender neutral. Given the large pre-existing gender gaps in employment, in absolute terms, more men lost employment than women. However, conditional on being employed pre-lockdown, women were roughly 20 percentage points less likely to be employed than men who were employed pre-lockdown. India has amongst the most unequal gender division of household work globally. Comparing hours spent on domestic work pre- and post-lockdown, I find that men increased hours spent on domestic work during lockdown. The male distribution continues to be right-skewed, but the proportions of men doing between 0.5 to 4 hours of housework per day increased post-lockdown. This seems to be driven by increased male unemployment. The time spent with friends decreased for both men and women, but relatively more for women.
Keywords: J1; J6; O53; 330; Covid-19; Lockdown; Employment; Gender; Time Use; India